Safety at the airports: KLIA case study - Omar, Amira; Sabar, Rohafiz (2012)
The purpose of the study is to determine the relationship between the factors that affects the safety and security of passengers and airport users. It’s concerned with the problem of security and its relation to operating equipment failures, operator negligence and damage to infrastructure. The problems of security at the airport are very important because, total uses of airplanes as the main transport to get out and enter the country are increasing day by day. So, many features of the airport safety and security concern for protecting the country from being attacked and invaded by terrorists.We use primary and secondary data. Primary data come from books, journals, and websites for information.Meanwhile, secondary data come from questionnaire and distribute to 100 respondents.This studies for review the passenger’s perceptions of quality of the safety and security at Kuala Lumpur International Airport (KLIA).